2019
DOI: 10.21608/mjcu.2019.54873
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and Determinants of “No-Mobile” Phobia (Nomophobia) among University Students

Abstract: Background: A simple random sample was followed to include the total required study sample at study colleges for both boys and girls. In each study college, the lists of students' names with their university IDs were used to select participant students. Selected students were personally contacted by the researcher, with the help of their tutors.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 7 publications
2
4
0
Order By: Relevance
“…In terms of the scientific evidence, the results are controversial. Some studies are consistent with the findings of the present study [ 5 , 38 , 39 ], while others did not observe statistically significant difference between genders with regards to nomophobia levels [ 14 , 40 , 41 , 42 , 43 , 44 ]. Regardless of ambiguity, gender discrepancies could be explained by the fact that men and women seem to use their smartphones differently.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…In terms of the scientific evidence, the results are controversial. Some studies are consistent with the findings of the present study [ 5 , 38 , 39 ], while others did not observe statistically significant difference between genders with regards to nomophobia levels [ 14 , 40 , 41 , 42 , 43 , 44 ]. Regardless of ambiguity, gender discrepancies could be explained by the fact that men and women seem to use their smartphones differently.…”
Section: Discussionsupporting
confidence: 92%
“…Regarding the frequency with which the participants were checking their phone, 36.1% were checking up to every 10 min and 18.8% every 20 min. This conclusion corresponds to preceding research findings showing that university students check their smartphone more frequently [ 5 , 22 , 41 , 43 ]. Additionally, a high percentage of the participants were using their smartphone when they were alone (93.8%), as similarly observed in recent study (93.7%) [ 48 ].…”
Section: Discussionsupporting
confidence: 92%
“…In Saudi Arabia, 85.3% of Health Sciences Colleges students were found to have mild to severe nomophobia, with 52.5% spending more than 2 h per day using their mobile phones (Al-Shalkh et al, 2019). Even further, about 82% ( n = 1,943) of sampled undergraduate students at King Saud University, Riyadh used their smartphones for more than 3 h per day (Alosaimi et al, 2016).…”
Section: Discussionmentioning
confidence: 99%
“…28 , 29 Moreover, a cross-sectional study conducted among health sciences students at King Khalid University in Saudi Arabia found that the incidence percentage of nomophobia was 85.3%, with 22.1% experiencing severe nomophobia and 63.2% suffering from mild nomophobia. 30 However, students of applied medical sciences were more vulnerable to severe nomophobia compared to students of medicine (34.4% vs 16.3%, respectively). 31…”
Section: Discussionmentioning
confidence: 98%